Tightening of the National and European Climate Targets to Achieve Greenhouse Gas Neutrality by 2045/2050 - Hans-Wilhelm Schiffer (Wirtschaftsdienst)
Abstract On the national and European level, the previous climate targets have been significantly tightened. The new requirements for achieving greenhouse gas neutrality in Germany by 2045 and in the EU-27 by 2050 are presented as well as the instruments with which the federal government and the EU intend to meet these goals. In the “Fit-for-55 package ” proposed by the EU Commission on 14 July, 2021, the introduction of a “Carbon Border Adjustment Mechanism ” (CBAM) is proposed to avoid “carbon leakage ”. The cornerstones of this proposal are outlined and evaluated. The conclusion is that the international agreement on a CO2 minimum price within the G20 would be clearly superior to the CBAM advocated by the EU Commission.